2000
DOI: 10.4141/s98-089
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil electrical conductivity on moisture determination using time-domain reflectometry in sandy soil

Abstract: The effect of soil electrical conductivity on moisture determination using time-domain reflectometry in sandy soil. Can. J. Soil Sci. 80: [13][14][15][16][17][18][19][20][21][22]. A series of laboratory experiments was conducted, in order to systematically explore the effect of soil electrical conductivity on soil moisture determination using time domain reflectometry (TDR). A Moisture Point MP-917 soil moisture instrument (E.S.I. Environmental Sensors Inc., Victoria, BC, Canada) was used to measure propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 17 publications
1
49
0
2
Order By: Relevance
“…Moreover, to achieve such results, TDR data needed to be filtered, omitting values of EC a that corresponded with unrealistic values of θ w (e.g., θ w = 0.80 cm 3 cm −3 and higher for sand; data not shown). This phenomenon was probably due to frequent irrigation events pushing down the concentrated solute front, thereby causing higher values of θ w and EC p (Dalton 1992;Sun et al 2000). Finally, a linear regression slope (value of 5.00 and 17.22 for the two salinity ranges) that significantly differed from the manufacturer recommended value of 6.4 indicated that a specific calibration would be needed to improve accuracy, as raised by previous authors in sandy soils (Ward et al 1994;Caron et al 1999).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, to achieve such results, TDR data needed to be filtered, omitting values of EC a that corresponded with unrealistic values of θ w (e.g., θ w = 0.80 cm 3 cm −3 and higher for sand; data not shown). This phenomenon was probably due to frequent irrigation events pushing down the concentrated solute front, thereby causing higher values of θ w and EC p (Dalton 1992;Sun et al 2000). Finally, a linear regression slope (value of 5.00 and 17.22 for the two salinity ranges) that significantly differed from the manufacturer recommended value of 6.4 indicated that a specific calibration would be needed to improve accuracy, as raised by previous authors in sandy soils (Ward et al 1994;Caron et al 1999).…”
Section: Resultsmentioning
confidence: 86%
“…A high soil electrical conductivity is also known to affect the accuracy and resolution of TDR water content measurements (Hook et al 2004). In a sandy matrix, TDR-based water content measurements were overestimated when EC p > 8 dS m −1 (Dalton 1992;Sun et al 2000). Moreover, depending on the geometry of the probes, differences in the measurement volume can also result in inconsistent results due to variable salt distribution over space (Robinson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Jacobsen & Schj0nning, 1993;Hook & Livingston, 1996), electrical conductivity (e.g. Dalton, 1992;Sun et al, 2000;Persson et al, 2000), and temperature (e.g. Pepin et al, 1995;Persson & Berndtsson, 1998).…”
Section: Open For Discussion Until 1 December 2001mentioning
confidence: 99%
“…This is within the range of PPs operating temperature (0-70°C). The electrical conductivity of the soil was less than 0.35 mS cm -1 , and was not expected to have an effect on the PP readings (Sun et al 2000).…”
Section: Methodsmentioning
confidence: 99%